Studies on Polyacrylonitrile-Methylcellulose Blend Based Electrolytes for Application in Symmetric Electrochemical Double Layer Capacitor - BAHARUDEAN, NUR NADIRAH (2021)
Solid polymer electrolytes (SPEs) for electrochemical double layer capacitor (EDLC) application have been extensively studies due to its favourable characteristic; light weight, solvent free and flexible. Despite these advantages, SPEs possess low mobility of charge carriers due to semi-crystalline nature of polymer. It has been reported that the ionic conductivity of SPE is lower than that of liquid electrolyte leading to poor electrochemical performance of EDLC. In the present work, , two polymer electrolyte systems consisting of polyacrylonitrile (PAN)-methylcellulose (MC) blend as a polymer host and lithium iodide (LiI) as ion source were prepared using solution cast technique. Two electrolyte systems were prepared; System I (undoped system) and System II (doped system). For System I, polymer blend-based films were prepared at various PAN: MC ratios to identify the most amorphous PAN-MC blend composition. The shifting of FTIR peak at 3436 cm-1 - 3466 cm-1 provided the evidence that PAN-MC interaction has taken place through hydrogen bonding between OH and C≡N group. From XRD result, 50:50 ratio of PAN: MC was found to be the most amorphous blend as it had the lowest percentage of crystallinity and crystallite size. FESEM analysis showed that PAN-MC blend films exhibited a single-phase structure inferring that the two polymers are miscible with one another. In System II, the complexation between the PAN-MC blend and Lil salt was confirmed through FTIR studies. From EIS analysis, the addition of 50 wt.% LiI (LiI50) obtained the highest room temperature conductivity of (8.12 + 1.57) x 10-4 S cm-1, which is in good agreement with results from XRD and FESEM. LSV analysis revealed that the maximum operational voltage of Li50 is 1.97 V, proving that the sample can be used in EDLC application. The electrochemical performance of the EDLC was tested using EIS and CV measurements.